Contemporary Philosophical Proposals for the University Toward a Philosophy of Higher Education (Springer International Publishing, 2018)
This edited collection brings together a robust range of philosophers who offer theoretically and critically informed proposals regarding the aims, policies, and structures of the university. The collection fills a major gap in the landscape of higher education theory and practice while concurrently reviving a long and often forgotten discourse within the discipline of philosophy. It includes philosophers from across the globe representing disparate philosophical schools, as well as various career stages, statuses, and standpoints within the university. There is also a diversity in method, approach and style, which varies from personal narratives and case studies, to philosophical genealogies, to traditional philosophical essays, and to systematic theories. The collection can serve as a theoretical resource for critically minded administrators and faculty who wish to analyze and change policies and structures at their home institutions. It will introduce them to a wide range of possible educational imaginaries, as well as provide them with productive suggestions for pragmatic change on campuses. .